Структурно-функціональні ознаки пластичності листків Typha angustifolia в залежності від умов зростання - Nedukha, Olena (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2025)
The results of the study of leaf anatomy and leaf epidermal ultrastructure of the heliophytic plant Typha angustifolia L. (Typhaceae), which grew in natural conditions: in the water on the bank of the Venetian Strait of the Dnipro River (Kyiv) and on land near the Strait, using light microscopy and scanning electron microscopy are presented. The common and distinctive features of the anatomical signs and the ultrastructure of epidermal cells of T. angustifolia leaves in the phase of vegetative growth of plants were revealed. The anatomical and morphological characteristics of leaves of two ecotypes of T. angustifolia that grew in water and on the terrestrial soil did not differ; the type of mesophyll and the presence of two zones in the epidermis (the zone of cоnvex vault and stomata zone) is stable features for this species. Differences in the size of the leaf blade, the density of stomata, and the density of wax coating on the surface of epidermal cells of the cоnvex vault zone, and also the presence of amorphous silicon in the cell walls of the epidermis are adaptive, and plastic traits that vary depending on the conditions of cattail growth. Besides, scanning electron microscopy of the leaf epidermis of cattail grown in water and on terrestrial soil revealed that growth in water causes the formation of stomata that are deepened into the epidermis, as well as the presence of closed stomata on the lower epidermis, while in the leaves of terrestrial cattail, all stomata were open and located at the same level as the regular epidermal cells. It is assumed that the deepening of stomata into the epidermis contributes to the optimal water balance of leaves under wave action of Strait and high humidity around the leaves of air-water cattail. The obtained results are discussed as a manifestation of phenotypic plasticity and the possible use of epidermal wax as an adaptive marker of heliophytes for growth in different water supply conditions.